PEMASARAN DAN UPAYA DALAM MEMPENGARUHI HARAPAN STAKEHOLDER DALAM LEMBAGA PENDIDIKAN ISLAM - Muhammad Mukhtar (Tarbawi : Jurnal Pendidikan Islam, 2017)
Marketing is an activity or approach that always oriented on consumers whoaim to make management decisions. Marketing should be done with careful planning and clear goals and oriented to customer satisfaction. Marketing in educational institutions is to establish a good image (image) of the institution and attract a number of prospective students. Marketing should be oriented to "customers" who in the context of a school or madrasah are called students/learners. This is where the need for a school or madrasah to find out how prospective students see the school or madrasah to choose. In addition, in order to know the needs and attract customers (students) then the strategic steps that can be done, namely market identification, market segmentation and positioning, product differentiation, marketing communications, and school services. The tool that can be used as a step in marketing is the 7P marketing mix that is composed of traditional 4P used in the marketing of goods and 3P as an expansion of the marketing mix. The 4P element is product; services such as what is offered, price; pricing strategy; place (location); where services are provided, promotion; how promotion is given. The 3P elements are people (people / human resources); quality, qualifications, and competencies held by persons engaged in the execution of services, physical evidence; facilities and infrastructure, such as what is owned, and process; management of the given learning. Pemasaran merupakan kegiatan atau pendekatan yang selalu berorentasipada konsumen dengan tujuan untuk membuat keputusan manajemen.Pemasaran hendaklah dilakukan dengan perencanaan matang, tujuanjelas, serta berorentasi pada kepuasan pelanggan. Pemasaran di lembagapendidikan adalah untuk membentuk citra (image) yang baik terhadaplembaga dan menarik minat sejumlah calon siswa. Pemasaran harusberorentasi kepada “pelanggan” yang dalam konteks sekolah ataumadrasah disebut dengan siswa/peserta didik. Disinilah perlunya sekolahatau madrasah untuk mengetahui bagaimana calon siswa melihat sekolahatau madrasah yang akan dipilihnya. Selain itu, dalam rangka mengetahuikebutuhan dan menarik pelanggan (siswa) maka langkah-langkah strategis yang dapat dilakukan, yaitu identifikasi pasar, segmentasi pasar dan positioning, diferensiasi produk, komunikasi pemasaran, dan pelayanan sekolah. Alat yang dapat dijadikan sebagai langkah dalam pemasaran adalah bauran pemasaran 7P yaitu terdiri dari 4P tradisional yang digunakan dalam pemasaran barang dan 3P sebagai perluasan bauran pemasaran. Unsur 4P yaitu product (produk); jasa seperti apa yang ditawarkan, price (harga); strategi penentuan harganya; place (tempat/lokasi); di mana tempat jasa diberikan, promotion (promosi); bagaimana promosi diberikan. Adapun unsur 3P yaitu people (orang/SDM); kualitas, kualifikasi, dan kompotensi yang dimiliki oleh orang yang terlibat dalam pelaksanaan jasa, physical evidence (bukti fisik); sarana dan prasarana, seperti apa yang dimiliki, dan process (proses); manajemen pembelajaran yang diberikan.